Let f ( x ) be a polynomial with f ( 1 ) = 1 . It has the property that for some integer k ∈ [ 1 , 2 0 1 5 ] ,
f ( f ( x ) ) = f ( x ) k
Define p ( x ) as the sum of all possible polynomials that satisfy these conditions. Find the value of the following sum: p ( x ) = 0 ∑ x 2 0 1 6
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The problem is misleading when it says "for any integer k ∈ [ 1 , 2 0 1 5 ] , f ( f ( x ) ) = f ( x ) k ." This makes it sound like the equation f ( f ( x ) ) = f ( x ) k is satisfied for all values of k ∈ [ 1 , 2 0 1 5 ] at the time. I think you mean "for some integer k ∈ [ 1 , 2 0 1 5 ] ."
Almost got tricked! I thought p ( x ) = n = 0 ∑ ⌊ 2 0 1 5 ⌋ x n so I got − 1 instead. I was reconsidering my answer again and again since this was a level 5 and seemed too easy (it should in fact be level 2/3, and I'll change that right now). Then, I saw that it was actually f ( f ( x ) ) = f ( x ) k rather than I whatever I thought it was. Anyhow, good problem :)
Keep on posting such nice questions :D
Let deg(f(x))=degree of f(x) f(f(x))=(f(x))^I, let deg(f(x))=n Therefore, deg(f(f(x)))=deg((f(x))^k) => n²=nk => n=0 or n=k. If n=0, f(x)=1 since f(1)=1. If n=k, f(f(x))=(f(x))ⁿ. Let 'a' be a root of f(x). Let f(x)=c(x-a1)(x-a2)...(x-an) Put x=a1, f(0)=(0)ⁿ=0, 0 is a root of f(x). Let an=0(we can choose any arbitrary ai=0). Therefore, cf(x)(f(x)-a1)...(f(x)-a(n-1))=cⁿxⁿ(x-a1)ⁿ.... Note xⁿ divides RHS, it must also divide LHS. But if all air's are nonzero then we cannot have linear factors of x. Thus we must make all roots of f(x) zero. Thus f(x)=cxⁿ. Putting this expression of f(x) in original equation we will get c=1. Thus f(x)=1,x,x²...x²⁰¹⁵. p(x)=1+x+x²+...+x²⁰¹⁵. Roots of p(x) are 2016th roots of unity except 1 itself, thus our final answer will be 2015
Problem Loading...
Note Loading...
Set Loading...
First, consider constant polynomials. f ( x ) = c for c = 0 or c = 1 satisfies that f ( f ( x ) ) = f ( x ) k , but the condition f ( 1 ) = 1 makes it so that only f ( x ) = 1 is valid.
For non-constant polynomials, let f ( x ) = z . Then we have that f ( z ) = z k which implies f ( x ) = x k . This also satisfies the condition that f ( 1 ) = 1 . With this part out of the way, we know that p ( x ) = 1 + x + x 2 . . . + x 2 0 1 5 then if we multiply by x − 1 we get: ( x − 1 ) p ( x ) = x 2 0 1 6 − 1 By definition, a root of the polynomial to the 2016th power must be 1 and there are 2016 roots. Therefore, by removing 1 2 0 1 6 : p ( x ) = 0 ∑ x 2 0 1 6 = 2 0 1 5